Analysis of Forest Area Changes in Langkat Regency - Agung Supriadi; Abdi Sugiarto (Yayasan Sinergi Multidimensi Kreatif, 2024)
This study aims to examine the Analysis of Forest Area Change in Langkat Regency. The method used in this study is an exploratory descriptive method, namely by holding collection, analysis and interpretation activities that aim to make a description. The data collected in this study consists of primary data and secondary data. In this study, the data collection technique uses several methods, including: Literature studies in general are the study of books related to the problem that is the subject of the research object. Data Reduction, Data Display and Conclusion Drawing / Verification. Deforestation and Conversion Research Results: Langkat Regency, like many other regions in Indonesia, has experienced significant deforestation and forest conversion for agriculture, plantations, and infrastructure development. Environmental Impacts: Changes in forest areas have an impact on the environment, including declining soil quality, declining biodiversity, and changing hydrological patterns. Management and Conservation: Forest management and conservation efforts are important to mitigate the negative impacts of forest area change. Policies and Regulations: Effective implementation of policies and regulations is essential to regulate land use and protect forest areas. Role of Local Communities: The involvement of local communities in forest management and decision-making related to land use can help ensure that changes are made taking into account ecological and social interests.